ANALISIS TINGKAT KESEHATAN BANK: METODE RISK-BASED BANK RATING (RBBR) - Puspitasari, Raja Gita; Rachmawati, Titiek (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This study aims to determine and analyze the soundness level of National Foreign Exchange Private Banks for 2017-2020 which is reviewed using the Risk-based Bank Rating method as a whole. This type of research is descriptive quantitative with research subjects at Foreign Exchange National Private Banks listed on the Indonesia Stock Exchange in 2017-2021. The data in this study uses secondary data in the form of financial reports from the Annual Report. The sampling technique used purposive sampling. The analysis technique used is the analysis of the health of the bank with a risk approach (Risk-based Bank Rating) with the scope of assessment based on the factors of Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. The results of the research on the Soundness Level of Foreign Exchange National Private Banks listed on the Indonesia Stock Exchange in 2017-2021 as a whole show healthy conditions with Composite Rating 1-2 achievements.